Renal Amyloidosis: Epidemiological, Clinical, and Laboratory Profile in Adults from One Nephrology Center - Hayet Kaaroud; Amel Harzallah; Mariem Hajji; Soumaya Chargui; Samia Barbouch; Sami Turki; Raja Trabelsi; Rim Goucha; Fatma Ben Moussa; Hedi Ben Maiz; Fethi Ben Hamida; Ezzeddine Abderrahim (International Journal of Nephrology)
Background. Renal amyloidosis is one of the main differential diagnoses of nephrotic proteinuria in adults and the elderly. The aim of this study with the most important series in our country is to contribute to the epidemiological, clinical, and etiological study of the renal amyloidosis. Methods. In a retrospective study carried out between 1975 and 2019, 310 cases of histologically proven and typed renal amyloidosis were selected for this study. Results. There were 209 men and 101 women with a mean age of 53.8 ± 15.4 years (range, 17–84 years). Of the 310 cases, 255 (82.3%) were diagnosed with AA renal amyloidosis and 55 (17.7%) with non-AA amyloidosis. Infections were the main cause of AA amyloidosis, and tuberculosis was the most frequent etiology. The period from the onset of the underlying disease to diagnosis of the renal amyloidosis was an average of 177 months. The most frequent manifestations at the time of diagnosis were nephrotic syndrome (84%), chronic renal failure (30.3%), and end-stage renal disease (37.8%). After a medium follow-up of 16 months (range, 0–68 months), mortality occurred in 60 cases. Conclusions. Given the high frequency of AA amyloidosis in our country, awareness of the proper management of infectious and chronic inflammatory diseases remains a priority in reducing the occurrence of this serious disease.